TRIM15 is a focal adhesion protein that regulates focal adhesion disassembly - Uchil, Pradeep D. (The Company of Biologists, 2014)
Focal adhesions are macromolecular complexes that connect the actin cytoskeleton to the extracellular matrix. Dynamic turnover of focal adhesions is crucial for cell migration. Paxillin is a multi-adaptor protein that plays an important role in regulating focal adhesion dynamics. Here, we identify TRIM15, a member of the tripartite motif protein family, as a paxillin-interacting factor and a component of focal adhesions. TRIM15 localizes to focal contacts in a myosin-II-independent manner by an interaction between its coiled-coil domain and the LD2 motif of paxillin. Unlike other focal adhesion proteins, TRIM15 is a stable focal adhesion component with restricted mobility due to its ability to form oligomers. TRIM15-depleted cells display impaired cell migration and reduced focal adhesion disassembly rates, in addition to enlarged focal adhesions. Thus, our studies demonstrate a cellular function for TRIM15 as a regulatory component of focal adhesion turnover and cell migration.